Assessing the Risk Level of the Challenges Faced In Construction Projects - Alameri, A.; Alhammadi, A. S. A. M.; Memon, A. H.; Rahman, I. A.; Nasaruddin, N. A. N. (Engineering, Technology & Applied Science Research, 2021)
The failure of construction projects could be attributed to several challenges that emerged during the construction process. Nine major challenges were uncovered from the literature: resource allocation, time, cost, quality, safety, project complexity, changes, uncertainties, and communication. A survey was carried out among professionals having a minimum of 10 years of experience in the construction industry to identify the occurrence and severity of these challenges. A total of 117 responses were analyzed and plotted on a risk matrix. The mean values indicated that time, cost, and quality are the top three challenges faced in construction projects, while the risk matrix revealed that all challenges are high-risk challenges. Thus, the professionals should consider suitable measures to address these challenges for improving a project’s performance.